Peircean semiotics and poetic production - Silveira, Lauro Frederico Barbosa da (2023)
Among the several semiotics and semiologies existing nowdays, there are two that must be distinguished: that of saussurean origin and that of peircean origin. The first finds its mode of proceeding and the general features of sign in the science of linguistics. The other belongs to the critical philosophic tradition. For the intelligence that can learn with the experience, the temporal and historic dimension is essential.The peircean sign supposes the relations of an irreversible time. To the present production of sign should be related the poetic function, which is essential to life of all intelligence. The scientific hypothesis, the social revolutions in their originary moment and the artistic production make new signs, draw new objects and open sets of possibilities for the conduct in the future.